2017
DOI: 10.15244/pjoes/66713
|View full text |Cite
|
Sign up to set email alerts
|

Differentiated Responses of Plankton and Zoobenthos to Water Quality Based on Annual and Seasonal Analysis in a Freshwater Lake

Abstract: In order to reveal the differentiated responses of plankton and zoobenthos to water quality on both annual and seasonal time scales, an ecological study on plankton and zoobenthos community was conducted during 2011 to 2015 in Nansi Lake in northern China. Different dynamics were found among phytoplankton, zooplankton, and zoobenthos in terms of density, biomass, and biodiversity. On an annual time scale and with deterioration of water quality, density and biomass of plankton and zoobenthos showed different va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…This study is similar to the study of [17] in China, where nutrients availability contributed to increase in phytoplankton biodiversity. However, [18] conducted a study in Nigeria wherein it was revealed that the increase in nutrients caused an increase in phytoplankton phyla being recorded; this is similar to the results of this study.…”
Section: B Phytoplankton Biodiversity Along Segment Of the Tshinanesupporting
confidence: 88%
“…This study is similar to the study of [17] in China, where nutrients availability contributed to increase in phytoplankton biodiversity. However, [18] conducted a study in Nigeria wherein it was revealed that the increase in nutrients caused an increase in phytoplankton phyla being recorded; this is similar to the results of this study.…”
Section: B Phytoplankton Biodiversity Along Segment Of the Tshinanesupporting
confidence: 88%
“…The primary nutrients, which influenced phytoplankton in Dongping Lake, changed from TN in spring to TP in summer. The growth of phytoplankton needs a suitable N/P ratio [42], and a previous study found that the N/P ratios in Dongping Lake changed from 5.17 to 9.64 [43]. Frau et al [44] pointed out that the control patterns of bottom-up and top-down effects on phytoplankton were different during different hydrological periods.…”
Section: Plos Onementioning
confidence: 99%
“…depletion of initially higher allochthonous nutrient contributing factors [4]. Therefore, dams and reservoirs tenaciously or inadvertently alter the downstream water quality.…”
mentioning
confidence: 99%